Empowering Data Transformation: Transforming Raw Data into A Strategic Planning for E-Commerce Success - Yang, Angelina; Wiratama, Jansen; Wijaya, Santo Fernandi (Journal of Information System and Informatics, 2024)
The ability to transform data is essential to support strategic decision-making in a company or organization. Data transformation can be done by utilizing data warehouse technology. Therefore, it is necessary to know the description of data warehouses that use the Extract, Transform, and Load (ETL) process. This research will focus on implementing Datawarehouse at TechTrove, an e-commerce company using Pentaho Data Integration (PDI). Star Schema organizes data marts and Online Analytical Processing (OLAP) to optimize data warehouse tasks. Business Intelligence (BI) tools are critical in extracting valuable insights and showcasing the platform's analytical capabilities in customer behavior analysis, product evaluation, sales monitoring, and inventory management. This research transformed raw data into a strategic plan to support decisions in E-Commerce companies.